2014
DOI: 10.1103/physrevlett.112.196801
|View full text |Cite
|
Sign up to set email alerts
|

Transport Properties of a 3D Topological Insulator based on a Strained High-Mobility HgTe Film

Abstract: We investigate the magnetotransport properties of strained 80 nm thick HgTe layers featuring a high mobility of μ ∼ 4 × 10 5 cm 2 =V · s. By means of a top gate, the Fermi energy is tuned from the valence band through the Dirac-type surface states into the conduction band. Magnetotransport measurements allow us to disentangle the different contributions of conduction band electrons, holes, and Dirac electrons to the conductivity. The results are in line with previous claims that strained HgTe is a topological … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
156
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(178 citation statements)
references
References 25 publications
16
156
0
3
Order By: Relevance
“…SdH oscillations have shown that σ xx oscillations at high B reflect the total carrier density in the TI, i.e., charge carrier densities in the bulk plus in top and bottom surfaces [7]. α total is directly proportional to C=A ¼ edn=dV g and corresponds to C=A ¼ eα total ¼ 1.22 × 10 −4 F=m 2 , a value close to the calculated capacitance C calc gt =A ¼ 1.45 × 10 −4 F=m 2 using thickness and dielectric constant of the layers [see Figs.…”
Section: -2mentioning
confidence: 99%
See 3 more Smart Citations
“…SdH oscillations have shown that σ xx oscillations at high B reflect the total carrier density in the TI, i.e., charge carrier densities in the bulk plus in top and bottom surfaces [7]. α total is directly proportional to C=A ¼ edn=dV g and corresponds to C=A ¼ eα total ¼ 1.22 × 10 −4 F=m 2 , a value close to the calculated capacitance C calc gt =A ¼ 1.45 × 10 −4 F=m 2 using thickness and dielectric constant of the layers [see Figs.…”
Section: -2mentioning
confidence: 99%
“…2(a). ρ xx displays a maximum near V g ¼ 1.5 V, whereas ρ xy changes sign; this occurs in the immediate vicinity of the charge neutrality point (CNP) [7]. The corresponding capacitance CðV g Þ at B ¼ 0 in Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While some TI compounds such as Bi 2 Se 3 and Bi 2 Te 3 show an insulating gap in their three-dimensional (3D) bulk band structure and so the Dirac cones can be studied at their 2D surface without modifying the material, a Mercury Telluride crystal does not have a 3D bulk band gap because the Fermi level resides within the four-fold degenerate Γ 8 band [5]. However, the topological insulation is realized by straining HgTe which opens a gap within the otherwise fourfold degenerate Γ 8 states [6,7] or growing the material in a HgTe/CdTe quantum well (QW) geometry [8][9][10]. In the latter case, CdTe (or Cd 1−x Hg x Te) barriers create quantum confinement within HgTe with the normal or inverted band structure depending on the well thickness, so that HgTe/CdTe QWs belong to the class of normal or topological insulators.…”
mentioning
confidence: 99%